Programa de vigilancia ambiental para bacterias formadoras de histamina en línea de atún precocido congelado de la empresa Marbelize S.A. - Zambrano Alcívar, Marcos Antonio (2020)
El The objective of this study was the design of an environmental monitoring programme for the control of histamine-forming bacteria from international standards, complying with the activities in accordance with the British Retailers Association's Global Food Safety Standard (BRC, 2018) applying criteria according to the International Commission on Microbiological Specifications for Food (ICMSF) , 2018), International Standardization Organization (ISO, 2018) number 18593, use of modified Niven's agar, modified Niven's broth, recognition of outliers using descriptive statistics and calculation of tolerance limits that includes alert and action limits. The cooling, conditioning, cleaning and packaging stage were recognized as exposed risk product stages, where sampling points were centralized in 4 zones. Within the 4 zones, 28 surface sampling points and 4 air sampling points were identified. Of the 28 surface sampling points, outlier results were found at 7 sampling points this represents 25% incidence. Regarding the microbiological results of histamine-forming bacteria in air samples, no incidence of atypical results was found. Alert and action limits were established for the control of histamine-forming bacteria in surface and air samples, being of great contribution to the food safety system.